Commodification of Women with Disabilities in Pond's Ads Your Face Edition Your Strength - Ria Anggraini; Denik Iswardani (MEDIASI : Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2023)
The purpose of this study is to interpret the commercialization practices of women with disabilities referred to in advertising, using John Fiske's semiotic approach, namely, the meaning of representation, the meaning of reality and the meaning of ideology in advertising. The commercialization of women in this advertisement can show that femvertising (feminist advertising) does not mean that women are not objectified. Instead of empowering women, the practice of femvertising further marginalizes women in media texts. The author argues that the femvertising strategy is a strategy that is not intended as a women's empowerment by building constructive messages, but only cloaks from capitalism by packaging advertisements using certain appeals to use the product. Thus, the perception of the product leads to purchasing decisions, which ultimately benefit the product.